HUBUNGAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR FISIKA DI SMA N 3 MUARO JAMBI - Fauziah Yolviansyah; Suryanti Suryanti; Endah Febri Setiya Rini; Maria Marisa Matondang; Sri Wahyuni (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2021)
This study ams to determine the relationship between interst in learning physics and student leraning outcomes. This research uses a quantutative research type, with the research instrument using a questionnaire. . The focus of this research is on 4 dimensions, namely the adoption of a scientific attitude, the pleasure of learning physics, and an interest in learning physics. The sample of this research was students of class XII MIA with a total of 60 students. This research was conducted at SMA N 3 MUARO JAMBI. Then, the data were analyzed using the SPSS 24 program to determine whether the data was normal, and using the Kolmogorov-Smirnov correlation test to see whether each variable had a relationship with one another. Based on research and test results from the Kolmogorov-Smirnov correlation test, a significance value of 0,000 was obtained. This means that the significance value of 0.000 <0.05, which indicates that the relationship between the two variables is very related or highly correlated.